A SLACKS-BASED MEASURE OF EFFICIENCY IN DATA ENVELOPMENT ANALYSIS TO ASSESS EFFICIENCY OF INDONESIAN SHARIA BANKS - M. Mujiya Ulkhaq (The Pontianak State Institute of Islamic Studies, 2023)
With the development of sharia banks, one of the effects that occurs is the existence of competition among sharia banks. The objective of this study is then to analyze the efficiency of sharia banks in Indonesia. Understanding the efficiency is important because if banks perform consistently with full efficiency, the less inputs they use, the larger output they achieve. The output is measured by total earning asset, while the inputs used are total deposit and total operating costs. A slacks-based measure of efficiency in data envelopment analysis is used to accomplish the objective of the research. Result shows that among twelve sharia banks under-investigated, four of them are considered as the most efficient.